Current topics in physics : in honor of Sir Roger J. Elliott - Symposium of Current Topics in Physics (2003 : Mexico City); Barrio, R. A. (Rafael A.); Kaski, K. (Kimmo); Elliott, R. J. (Roger J.), 1928- (London : Imperial College Press ; Singapore ; Hackensack, NJ : Distributed by World Scientific, 2005)
This indispensable book is a compilation of invited talks delivered at the symposium, "Current Topics in Physics" held in Mexico City in June 2003, to celebrate the 75th birthday of Professor Sir Roger Elliott. The contributions have been prepared by research associates, former students, post-doctoral fellows and colleagues of Professor Elliott, many of them leading scientists - as Sir Roger himself - in important research institutes around the world. The book gives a very timely and comprehensive overview of various key areas of modern condensed matter and statistical physics. 19 original contributions are included, grouped in three main areas: disorder and dynamical systems, structures and glasses, electrical and magnetic properties. The contributions are by many of the foremost researchers in the field of condensed matter and statistical physics. In particular, contributions by such prominent scientists as M E Fisher, A A Maradudin, M F Thorpe, M Balkanski, T Fujiwara, and of course Sir Roger Elliott himself make this book a rewarding read.
Order and disorder in physics : inauguration speech / Roger Elliott -- Ch. 1. Reflections on the beguiling but wayward spherical model / M.E. Fisher -- Ch. 2. Phase transitions in vector spin glasses / A.P. Young -- Ch. 3. Transitions, dynamics and disorder : from equilibrium to nonequilibrium systems / R. Stinchcombe -- Ch. 4. Two-dimensional growth in a three component mixture with competing interactions / C. Varea -- Ch. 5. Glassy dynamics at the edge of chaos / A. Robledo -- Ch. 6. Flexibility in biomolecules / M.F. Thorpe, M. Chubynksy, B. Hespenheide, S. Menor, D.J. Jacobs, L.A. Kuhn, M.I. Zavodszky, M. Lei, A.J. Rader and W. Whiteley -- Ch. 7. Lattice dynamics of carbon nanotubes / V.N. Popov and M. Balkanski -- Ch. 8. Glassy behavior due to kinetic constraints : from topological foam to backgammon / D. Sherrington -- Ch. 9. On glass transition with rapid cooling effects / R. Kerner and O. Mares -- Ch. 10. The dielectric loss function and the search for simple models for relaxation in glass formers / A.P. Vieira, M. Lopez de Haro, J. Taguena-Martinez and L.L. Goncalves -- Ch. 11. The theory of Turing pattern formation / T. Leppanen -- Ch. 12. The dioctadecylamine monolayer : non-equilibrium phase domains / A. Flores, E. Corvera-Poire, C. Garza and R. Castillo -- Ch. 13. Multiple scattering effects in the second harmonic generation of light reflection from a randomly rough metal surface / A.A. Maradudin, T.A. Leskova, M. Leyva-Lucero and E.R. Mendez -- Ch. 14. Theory for large-scale electronic structure calculations / T. Fujiwara, T. Hoshi and R. Takayama -- Ch. 15. Symmetric magnetic clusters / J.B. Parkinson, R.J. Elliott and J. Timonen -- Ch. 16. Optical and Fermi-edge singularities in one-dimensional semiconductor quantum wires / K.P. Jain -- Ch. 17. Probing the magnetic coupling in multilayers using domain wall excitations / A.S. Carrico and A.L. Dantas.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Physics -- Congresses; Physique -- Congrès.; SCIENCE -- Physics -- General; SCIENCE -- Mechanics -- General; SCIENCE -- Energy; Physics; Conference papers and proceedings